Green Accounting Leads to Sustainable Companies - Shankar Subramanian Iyer; Raman Subramanian; Meenakshi Dhoundiyal; Arpita Mehrotra (Indonesian Journal of Sustainability Accounting and Management, 2024)
The aim of this study is to explore the concept of green accounting and its impact on the sustainability of companies. Green accounting is an approach that seeks to integrate environmental considerations into traditional accounting practices. The research study uses mixed methodology to get consensus on the conceptual model and hypotheses formulated. By considering the environmental impacts of a company's operations, green accounting provides a more accurate picture of a company's financial performance. This paper argues that companies that adopt green accounting practices are more likely to operate sustainably, as they are able to identify and address environmental risks and opportunities more effectively. Green accounting is essential for companies seeking to operate sustainably and recommends that more companies adopt this approach to ensure long-term viability and success. The study advances methodologies, encourage interdisciplinary collaboration, guide practical corporate sustainability efforts, influence financial reporting standards, raise stakeholder awareness, and potentially shape policies to foster a more sustainable business environment. The study contributes to the Page 2 of 2 topic area to incorporate environmental costs and benefits into financial reporting to raise funds legitimately from the environment disaster defaulters.